Purely electronic insulator-metal transition in rutile VO2 - Shaobo Cheng; Henry Navarro; Zishen Wang; Xing Li; Jasleen Kaur; Alexandre Pofelski; Qingping Meng; Chenyu Zhou; Chi Chen; Mark P. M. Dean; Mingzhao Liu; Ali C. Basaran; et al. (Nature Communications)
Abstract Volatile resistive switching in neuromorphic computing can be tuned by external stimuli such as temperature or electric-field. However, this type of switching is generally coupled to structural changes, resulting in slower reaction speed and higher energy consumption when incorporated into an electronic device. The vanadium dioxide (VO2), which has near room temperature metal-insulator transition (MIT), is an archetypical volatile resistive switching system. Here, we demonstrate an isostructural MIT in an ultrathin VO2 film capped with a photoconductive cadmium sulfide (CdS) layer. Transmission electron microscopy, resistivity experiments, and first-principles calculations show that the hole carriers induced by CdS photovoltaic effect are driving the MIT in rutile VO2. The insulating-rutile VO2 phase has been proved and can remain stable for hours. Our finding provides a new approach to produce purely electronically driven MIT in VO2, and widens its applications in fast-response, low-energy neuromorphic devices.